THE RELATIONSHIP BETWEEN MUSIC AND MOVEMENT IN EDUCATION - Dalma TOADERE KOVÁCS (Studia Universitatis Babeş-Bolyai. Musica, 2018)
This study first presents the role of music and movement in the education of ancient Greece, based on Plato and Aristotle’s philosophic views. These views had a major impact on most of the representatives of music education in the twentieth century: Émile Jaques-Dalcroze, Zoltán Kodály and Carl Orff. We summarized their pedagogical contribution concerning general music education, stressing especially the importance they attach to the relationship between music and movement.